PENGARUH UKURAN PASIR TERHADAP KINERJA BOILER UNIT 1 PLTU PULANG PISAU - Karno Karno; Achmad Kusairi Samlawi (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2019)
The use of sand in the cfb boiler function as a coal burner which enters the combustion chamber. Sand in the combustion chamber is lined up and coal enters the combustion chamber. With the entry of coal into the furnace fluidization occurs, where the heat in the sand burns coal that hovers, so that the heat that arises is used to heat the water in the boiler tubes. The remaining coal combustion (ash) wil float/fly inhaled by IDF air. Sand movement is expeted to only always bubbling up ang down in the furnace area only so that complete combustion occurs and the boiler is reliable. Because the bubbling is influenced by air pressure, coal quality, which can cause friction between material (sand and coal) and refractory giving rise to abrasives on refractory. If refractory is abrasive it can cause abrasive on the tube water wall boilers, tube cyclones so that boiler performance will decrease.The use of sand that is not clear is one of the causes of refractory damage in cfb type boilers. So that the cfb boiler remains reliable, the use of sand must be in accordance with the type and size according to the particular boiler.